EFFECT OF PH ON TRANSEPITHELIAL ELECTRICAL PARAMETERS IN SEAWATER-ADAPTED EEL INTESTINE - TRISCHITTA, Francesca Ross; DENARO, Maria Gabr.; FAGGIO, Caterina; FUCILE F; SCHETTINO T. (Journal of Comparative Physiology B, 1994)
The sensitivity to external pH of Cl- absorption was studied in isolated stripped intestinal mucosa of the eel, Anguilla anguilla, mounted in Ussing chambers. Short-circuit current, transepithelial potential difference and conductance were measured in bathing solutions containing various combinations of HCO3--concentration (0-25 mmol.l(-1)), partial pressure of CO2 (0-76 mm Hg) and pH (6.9-7.9). A linear relationship was found between pH and short-circuit current in the range of pH studied both in HCO3-/CO2 Ringer and in Hepes Ringer. The pH effect was almost completely reversible. It was not affected by the presence of mucosal Ba2+ (10(-3) mol.l(-1)) but it was inhibited by the presence of luminal (10(-5) mol.l(-1)) or serosal (10(-4) mol.l(-1)) bumetanide. The results obtained suggest that the Cl- absorption in the European eel intestine is pH sensitive. The data do not indicate whether the pH affects directly the Na+-K+-Cl- cotransport and/or the basolateral Cl- conductance or other mechanisms indirectly linked to Cl- absorption.